The Positive Role of School Climate on School Victimization, Depression, and Suicidal Ideation Among School-Attending Homeless Youth. (3rd July 2018) - Moore, Hadass; Benbenishty, Rami; Astor, Ron Avi; Rice, Eric
ABSTRACT: Although homeless youth face a higher risk of victimization and mental health problems, little is known about school victimization and mental health outcomes for school-attending homeless youth. This study examined the relationship between school climate and school-related victimization and mental health problems among homeless youth. Multivariate analyses were conducted to examine the relationship between school climate factors and school victimization, suicidal ideation, and depression tendency in a representative sample of 1, 169 school-attending homeless youth in 9th and 11th grades in California. Findings show that school-attending homeless youth are at high risk of being victimized at school and have high rates of depression tendency and suicidal ideation. Positive school climate, especially perceived high expectations from teachers and safety in school, was associated with lower rates of school victimization and mental health problems. The role of supportive school climate in the lives of school-attending homeless youth is discussed and future implications are suggested.